Post-Exercise Recovery: Fundamental and Interventional Physiology - Sergej M. Ostojic (Frontiers Research Topics, 2016)
Physiological responses after maximal and submaximal exercise are routinely monitored in a plethora of diseases (e.g. cardiovascular diseases, cancer, diabetes, asthma, neuromuscular disorders), and normal populations (e.g. athletes, youth, elderly), while slower or irregular post-exercise recovery usually indicates poor health and/or low fitness level. Abnormal post-exercise recovery (as assessed via blunted post-exercise heart rate dynamics) helps to predict the presence and severity of coronary artery disease, while differences in recovery outcomes in athletes might discriminate between fit and unfit individuals. Disturbances in post-exercise recovery might be due to acute or persistent changes in: (1) adaptive responses mediated by the autonomic nervous system and vasodilator substances, (2) cellular bioenergetics, and/or (3) muscular plasticity. Preliminary evidence suggests possible role of time-dependent modulation of nitric oxide synthase and adenosine receptors during post-exercise recovery, yet no molecular attributes of post-exercise recovery are revealed so far. Currently several markers of post-exercise recovery are used (e.g. heart rate measures, hormone profiles, biochemical and hematological indices); however none of them meets all criteria to make its use generally accepted as the gold standard. In addition, recent studies suggest that different pharmacological agents and dietary interventions, or manipulative actions (e.g. massage, cold-water immersion, compression garments, athletic training) administered before, during or immediately after exercise could positively affect post-exercise recovery. There is a growing interest to provide more evidence-based data concerning the effectiveness and safety of traditional and novel interventions to affect post-exercise recovery. The goals of this research topic are to critically evaluate the current advances on mechanisms and clinical implications of post-exercise recovery, and to summarize recent experimental data from interventional studies. This knowledge may help to identify the hierarchy of key mechanisms, and recognize methods to monitor and improve post-exercise recovery in both health and disease.